Comparison of Efficacy of Vonoprazan Versus Esomeprazole in Patients with Helicobacter Pylori Infection - Shahzad, Khurram; Attique Abou Bakr, (Indus Journal of Bioscience Research, 2025)
Introduction: Helicobacter pylori (H. pylori) infection causes gastritis, ulcers, and gastric cancer. Treatment typically involves PPIs like Esomeprazole, but newer P-CABs like Vonoprazan have shown potential. A study compared Vonoprazan and Esomeprazole effectiveness in H. pylori eradication. Methodology: 180 H. pylori-infected patients were randomly divided into Group A receiving Esomeprazole-based therapy and Group B receiving Vonoprazan-based therapy. Response to treatment was assessed by H. pylori eradication rates, with statistical analysis comparing efficacy across demographic and clinical factors. Results: Vonoprazan (87.8%) was significantly more effective than Esomeprazole (72.2%) (p = 0.009). Subgroup analysis favored Vonoprazan in males (p = 0.001), younger patients (p = 0.006), normal BMI (p = 0.005), longer disease duration (p = 0.036), and smokers (p = 0.001). No significant differences were found in females, older patients, overweight individuals, or those with high blood pressure. Conclusion: Vonoprazan demonstrated superior efficacy in eradicating Helicobacter pylori compared to esomeprazole, with a statistically significant higher success rate (87.8% vs. 72.2%, p=0.009). The findings suggest that vonoprazan may be a more effective alternative, particularly in males, younger individuals, smokers, and those with normal BMI or longer disease duration. These results highlight the potential of vonoprazan-based therapy in overcoming challenges associated with bacterial resistance and inadequate acid suppression. Further studies with larger populations and diverse demographics are warranted to validate these findings and support the inclusion of vonoprazan in standard treatment protocols for H. pylori eradication.